Effect of tillage and nitrogen management on yields, profitability and nitrogen balance of baby corn (Zea mays) - RAM, HARDEV; KUMAR, RAKESH; MEENA, RAJESH KUMAR; MALIK, RAMAN; MALLIKARJUN, MALLIKARJUN; SAXENA, ANURAG (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was carried out during kharif 2016 and 2017 at ICAR-NDRI, Karnal to evaluate the effect of tillage and nitrogen management on productivity, quality and profitability of baby corn (Zea mays L.). The experiment consisted of 18 treatments comprising three tillage practices, viz. zero tillage (ZT), conventional tillage (CT) and raised beds (RB) as main plots while six nitrogen (N) management practices, viz. control, N75%, N75+Azotobactor, N100%, N100+Azotobactor and N125% were assigned in sub-plots in split plot design with three replications. Among tillage practices, RB showed significantly higher yield attributes, yield, green fodder (376.7 q/ha) and baby cobs yield (10.3 q/ha) over CT (346.7 and 8.38 q/ha) and ZT (363.6 and 9.36 q/ha). Among the N management options, increasing N levels increased growth and yield attributes and yield up to 100% N with application of Azotobactor. The maximum pooled cost of production was recorded under CT followed by RB and lowest in ZT. However, mean net return was observed highest under RB (`111.9 lakh/ha) followed by ZT (`103.6 lakh/ha) and lowest in CT (`89.3 lakh/ha). The saving in total cost of cultivation due to ZT was `900 to 2,500/ha, as compared to RB and CT, respectively. Hence, to realize higher productivity, profitability and sustain soil health, baby corn planted under raised bed with application of 100% N with azotobactor was quite cost efficient, this can further strengthen and sustain the performance of livestock in terms of quality green fodder availability.